Determinants of Loan Repayment Among Microfinance Beneficiaries in Lagos State, Nigeria - O. Olateju, Adijat (MultiTech Publisher, 2024)
This study examines the determinants of loan repayment among microfinance institutions (MFIs) among their 384 microenterprises. The research found that age, gender, marital status, educational level, business experience, family size, type of business, interest rate, profit level, lending method, training/business enhancement program, and loan repayment time are not significant determinants of loan repayment among MEs in the study area. Prompt loan repayment can encourage cordial relationships between MFIs and their customers, and thus, MFIs and stakeholders should consider these significant variables when extending loans to their clients. This highlights the importance of timely loan repayment for MFIs' survival and growth.